Abscisic Acid Regulates Auxin Distribution to Mediate Maize Lateral Root Development Under Salt Stress - Lu, Chongchong (Front Plant Sci, 2019)
Roots are important plant organs. Lateral root (LR) initiation (LRI) and development play a central role in environmental adaptation. The mechanism of LR development has been well investigated in Arabidopsis. When we evaluated the distribution of auxin and abscisic acid (ABA) in maize, we found that the mechanism differed from that in Arabidopsis. The distribution of ABA and auxin within the primary roots (PRs) and LRs was independent of each other. Auxin localization was observed below the quiescent center of the root tips, while ABA localized at the top of the quiescent center. Furthermore, NaCl inhibited LRI by increasing ABA accumulation, which mainly regulates auxin distribution, while auxin biosynthesis was inhibited by ABA in Arabidopsis. The polar localization of ZmPIN1 in maize was disrupted by NaCl and exogenous ABA. An inhibitor of ABA biosynthesis, fluridone (FLU), and the ABA biosynthesis mutant vp14 rescued the phenotype under NaCl treatment. Together, all the evidence suggested that NaCl promoted ABA accumulation in LRs and that ABA altered the polar localization of ZmPIN1, disrupted the distribution of auxin and inhibited LRI and development.